Pap smear as early diagnostic tool for cervical cancer- A life saviour - Dr. Shwetha Ramu; Dr. Bindu B. J.; Murthy, Narayana (Tropical Journal of Pathology and Microbiology, 2018)
Background: Cervical cancer is a leading cause of mortality and morbidity among women globally and most common gynaecological cancer in developing countries. Papanicolaou smear study is a simple and cost effective screening test for cervical cancer. The aim of this study is to evaluate and interpret the pattern of cervical Pap smear cytology in a tertiary hospital. The interpretation and reporting of the Pap smear is based on 2001 Bethesda system. Materials and Methods: This is a retrospective study conducted at Department of Pathology, Basaveshwara Medical College, Hospital and Research Centre, Chitradurga, Karnataka, India. The study was conducted over a period of two years from June 2015 to May 2017. All pap smears received in the department of Pathology during study period were included. Results: A total of 2210 pap smears were reported in the study period. Majority of the cases were inflammatory smears (35.88%) and Negative for Intraepithelial lesion or malignancy (49.86%). Candidiasis, Bacterial vaginosis, Trichomonas vaginalis, atrophy and reactive cellular changes associated with inflammation were seen in 0.49%, 0.72%, o.36%, 8.91% and 0.40% cases respectively. 0.31% Vault smears were studied. Epithelial cell abnormalities (1.4%) include Atypical squamous cells of undetermined significance (0.4%), Low grade squamous intraepithelial lesion (0.63%) and High grade intraepithelial lesion (0.31%). 88% of Low grade squamous intraepithelial lesion was seen in reproductive age group (18-50 years). Conclusion: Cervical cancer is the most common gynaecological cancer in the developing countries. Pap smear is the simple, easy and cost effective screening tool to detect premalignant and malignant cervical lesions, and reduce the mortality due to cervical cancer by early diagnosis and treatment.